Changes in the excitability of the medial parabrachial nucleus neurons during the chronic phase of pilocarpine-induced epilepsy in mice - Xiao, Jinyu; Gu, Yinghui; Quan, Chunhua; Li, Shulei; Liang, Jianmin (Frontiers in Pharmacology, 2025)
IntroductionEpilepsy is a common and serious brain disorder that often co-occurs with sleep disturbances. Sodium valproate, a conventional antiepileptic drug, alleviates sleep disorders in patients with epilepsy; however, the exact underlying mechanism remains unclear. The medial parabrachial nucleus is a crucial brain structure that regulates sleep-phase transitions. However, its role in pathogenesis of epilepsy remains uncertain. Therefore, we aimed to investigate whether medial parabrachial nucleus excitability is elevated during the chronic phase of temporal lobe epilepsy and whether sodium valproate could alleviate the pathological changes associated with temporal lobe epilepsy by modulating neuronal excitability in the medial parabrachial nucleus.MethodsWe used the whole-cell current clamp technique to investigate the excitability of the medial parabrachial nucleus in a mouse chronic epilepsy model. To validate our findings, we utilized immunofluorescence staining and Western blotting to detect changes in the expression of FosB, a marker of neuronal activity, and glial fibrillary acidic protein (GFAP), a marker of reactive astrocyte proliferation, in the medial parabrachial nucleus during the chronic phase of epilepsy. We conducted a 28-day continuous gastric lavage of sodium valproate for antiepileptic treatment and observed changes in the excitability of neurons in the medial parabrachial nucleus neurons and the expression of FosB protein and GFAP after drug treatment.ResultsWe observed that medial parabrachial nucleus neurons in slices from mice that received pilocarpine stimulation fired more action potentials than those in slices from control animals that received saline. However, after treatment with sodium valproate, the number of generated action potentials decreased significantly. Immunofluorescence staining and Western blotting data on FosB and GFAP expression confirmed the increased excitability of medial parabrachial nucleus neurons and enhanced astrocyte reactivity during the chronic epilepsy phase.ConclusionOur findings indicate an increase in the excitability of medial parabrachial nucleus neurons, along with increased reactivity of astrocytes in the chronic epilepsy model. Sodium valproate may improve the symptoms of temporal lobe epilepsy and reduce seizures by inhibiting medial parabrachial nucleus neuronal excitability. These results deepen our understanding of the pathogenesis of temporal lobe epilepsy and provide new perspectives and strategies for further research.